POLITE REQUEST STRATEGIES BY MALE AND FEMALE OF ENGLISH LEARNERS - Habibi, Fajri (JURNAL SMART, 2017)
The present study investigated request strategy by non-native English speakers. The study focused at the rank of imposition in the choice of request and politeness strategy between twenty five males and females of postgraduate English students Muhammadiyah University of Surakarta. The data were collected by discourse completion tests (DCT) which consisted of six situations. Their responses were categorized using the scale of Trosborg request theory and Brown and Levinson politeness. The findings showed that the students utilized hearer oriented conditions strategy when uttered to the hearer with higher status. However, the male students tended to use direct request strategy in the situation when they had high position status. The combination request strategy was used to pressure the intention of request utterance. The male and female students also used some supportive moves in their utterance.